1992
DOI: 10.1126/science.258.5086.1335
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Detection of the Period-Four Cycling of the Manganese Cluster in Photosynthetic Water Oxidizing Enzyme

Abstract: X-ray absorption near-edge structure spectra of the manganese (Mn) cluster in physiologically native intermediate states of photosynthetic water oxidation induced by short laser flash were measured with a compact heat-insulated chamber equipped with an x-ray detector near the sample surface. The half-height energy of the Mn Kedge showed a period-four oscillation dependent on cycling of the Joliot-Kok's oxygen clock. The flash number-dependent shift in the Mn K-edge suggests that the Mn cluster is oxidized by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
207
1
4

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(232 citation statements)
references
References 21 publications
19
207
1
4
Order By: Relevance
“…Mn(1)ZIV, Mn(2)ZIV, Mn(3)ZIII, Mn(4)ZIII) and model (b) where an additional water ligand is completing the hexacoordinated shell of Mn(4) and the oxidation states are Mn 4 (IV,III,III,IV ). These results are partially consistent with EPR and X-ray spectroscopic evidence (Ono et al 1992;Yachandra et al 1993;Roelofs et al 1996;Bergmann et al 1998;Iuzzolino et al 1998;Dau et al 2001;Messinger et al 2001) but disagree with the suggested low-valent Mn 4 (III,III,III,III ) state (Zheng & Dismukes 1996;Kuzek & Pace 2001).…”
Section: Structural Models Of the O 2 -Evolving Centresupporting
confidence: 73%
“…Mn(1)ZIV, Mn(2)ZIV, Mn(3)ZIII, Mn(4)ZIII) and model (b) where an additional water ligand is completing the hexacoordinated shell of Mn(4) and the oxidation states are Mn 4 (IV,III,III,IV ). These results are partially consistent with EPR and X-ray spectroscopic evidence (Ono et al 1992;Yachandra et al 1993;Roelofs et al 1996;Bergmann et al 1998;Iuzzolino et al 1998;Dau et al 2001;Messinger et al 2001) but disagree with the suggested low-valent Mn 4 (III,III,III,III ) state (Zheng & Dismukes 1996;Kuzek & Pace 2001).…”
Section: Structural Models Of the O 2 -Evolving Centresupporting
confidence: 73%
“…However, on the basis of Mn K-edge studies, other groups have proposed that Mn is oxidized during the S 0 →S 1 , S 1 →S 2 , and also during the S 2 →S 3 transitions. 17,18 The requirement of a higher signal-to-noise ratio for the EXAFS relative to the XANES experiments has made EXAFS measurements more difficult for the flash-induced S state samples. Earlier EXAFS data from the chemically treated S 3 state samples produced by a double-turnover method indicated that the two di-μ-oxo-bridged Mn-Mn dimer units may become nonequivalent.…”
Section: Introductionmentioning
confidence: 99%
“…119 Mn K-edge x-ray absorption near edge structure (XANES) has been used to probe the Mn valence at the different S states. 19,20,115,141 The Mn K-edge positions for the S 0 , S 1 and S 2 states have been determined as inflection-point energies from second derivative zero-crossings 142 and the overall edge shape is consistent with oxygen ligation. 107 The shifts in edge position, along with characteristic changes in the edge shapes are indicative of Mn oxidation, so that the proposed Mn oxidation state assignments are as follows: S 0 (II, III, IV, IV) or (III, III, III, IV), S 1 (III, III, IV, IV), and S 2 (III, IV, IV, IV).…”
Section: Introductionmentioning
confidence: 99%
“…Much has been learned about the catalytic Mn cluster, and a working model has been proposed 11,[16][17][18] based mainly on X-ray absorption spectroscopy (XAS) and electron paramagnetic resonance (EPR) studies. Both X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) experiments have focused on the Mn atoms of the OEC to obtain oxidation states, 19,20 and structural information about this active site. [21][22][23][24][25][26] Along with manganese and chloride, Ca is an essential cofactor in oxygen evolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation